PENGEMBANGAN MEDIA PEMBELAJARAN IPA MENGGUNAKAN COCOPOT DARI LIMBAH SABUT KELAPA PADA MATERI PERTUMBUHAN TANAMAN DI KELAS IV SDN 101777 SAENTIS - Juhaira Amsar Hrp; Zainuddin Muchtar; Fahrur Rozi; Suyit Ratno; Syahrial (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop science learning media in the form of cocopot derived from coconut fiber waste on plant growth material in grade IV of elementary school and to determine the level of validity, practicality, and effectiveness. This study uses a 4D development model (Define, Design, Development, Disseminate). The subjects of the study were 15 grade IV students of SDN 101777 Saentis. Data collection techniques were interviews, observations, questionnaires and tests. Data analysis techniques were carried out using qualitative and quantitative analysis. The results of the study showed that (1) the cocopot learning media was declared valid with the validation results of material experts of 85% and media experts of 96% with the criteria of "very feasible"; (2) the cocopot learning media was declared practical based on teacher responses with a percentage of 92% included in the criteria of "very practical"; and (3) the cocopot learning media was declared effective, indicated by the increase in student learning outcomes, where the average pre-test score of 53.3% increased to 87.6% in the post-test. Furthermore, during the dissemination phase, there was an increase from 47.3% to 86.7%, with an N-Gain value of 0.757, or 75.7%, which is considered high. Thus, the cocopot learning media made from coconut fiber waste has proven valid, practical, and effective for use in science teaching on plant growth in elementary schools and significantly improves student learning outcomes